Contextualizing Buccal Dental Microwear Variations During the Byzantine Period in Jordan - Mohammad Alrousan; Ali Khwaileh; Abdulla Al-Shorman (Dental Anthropology Association, 2014)
This study scanned 14 buccal surfaces of teeth casts microscopically from the Byzantine sites of Yajuz and Sa'ad in Jordan, and 7 samples from the Natufian site of El Wad in Palestine for the purpose of studying buccal microwear. The results show no differences in the pattern of dental microwear between the two byzantine sites, while a difference was existed when these sites com-pared to El Wad. The results indicate that subsistence economy did not trigger buccal microwear but cultural development. Although the economies during the Byzantine period were diversified, technological adaptation diffused into region, which eased food accession and procession.